IMPROVEMENT OF MEANS FOR MECHANICAL THERAPY OF THE LOWER LIMBS - Neverov, Evgeny Nikolaevich; Plotnikov, Konstantin Borisovich; Plotnikov, Igor Borisovich; Neverova, Tatyana Vladimirovna; Yakovlev, Sergey Vladimirovich (Medicine in Kuzbass, 2026)
In modern trauma and orthopaedic practice, the role of post-operative rehabilitation as a distinct clinical phase is steadily increasing. However, early mobilisation of the ankle joint – a proven method for preventing contractures and joint fibrosis – remains difficult to achieve: an analysis of commercially available CPM devices has shown that the average weight of these devices exceeds 12 kg, and the vast majority of designs are intended exclusively for use in a ‘seated’ position, which precludes their use in the acute postoperative period when strict bed rest is required.The aim of the study is to develop and validate the architecture of a compact, passive-action mechanotherapy device free from the aforementioned limitations.Materials and methods. The work was carried out using a systematic approach integrating biomechanical analysis of ankle joint movements, the synthesis of multi-link kinematic schemes using methods from the theory of mechanisms and machines, finite element analysis of load-bearing components, and topological optimisation of the design. The load-bearing components were manufactured using the fused deposition modelling (FDM) method from a carbon-fibre-reinforced PETG composite (PETG-CF).Results. A prototype device for passive mechanotherapy of the ankle joint has been designed and manufactured. The proposed multi-link kinematic scheme with a variable instantaneous centre of rotation reproduces foot movements within a plantar flexion range of 0-40° and dorsiflexion range of 0-20°, with a trajectory error of no more than 2.5°. The use of additive manufacturing and topological optimisation has reduced the total weight of the device to 5 kg with dimensions of 400 × 350 × 450 mm. The modular design allows rehabilitation sessions to be conducted in both a «sitting» and «lying» position.Conclusion. The developed device fills the functional gap between bulky stationary CPM machines and wearable exoskeletons for active walking, enabling early passive mobilisation directly at the patient’s bedside. A multi-level overload protection system and the ability to programme individual protocols create the conditions for clinical testing of the device in both inpatient and outpatient rehabilitation settings.
Keywords: mechanotherapy; CPM therapy; rehabilitation; ankle joint; additive manufacturing; topological optimization; biomechanics